Strategies for Preventing Terrorism Attacks in the Capital City of Nusantara - Yuanita Retno Satuti; Sapto Priyanto (Dinasti Research, 2025)
The relocation of Indonesia’s capital from Jakarta to East Kalimantan aims to address challenges such as environmental risks, pollution, congestion, and overpopulation. Nusantara (IKN) is designed as a new administrative hub to promote economic equality, regional development, and sustainability. However, this transition also introduces security risks, particularly from Jamaah Ansharut Daulah (JAD), a terrorist group with a history of attacks in East Kalimantan. A comprehensive security strategy is crucial to protect IKN from potential terrorist threats. This study applies the PPRR (Prevention, Preparation, Response, Recovery) theory using a qualitative approach, analyzing data from scientific journals, government reports, and other publications. Findings indicate that IKN faces a medium risk of attack. While an immediate attack is unlikely, potential consequences include physical damage, casualties, and national instability. Key risk factors include IKN's strategic location, past terrorist activities in the region, and security infrastructure vulnerabilities. To mitigate these risks, strategic measures are needed, including enhancing intelligence capabilities, reinforcing security in IKN, and addressing ideological threats. Implementing a PPRR-based strategy is essential for stability, minimizing attack risks, and ensuring long-term security, allowing IKN to emerge as a resilient symbol of national governance.